Targeted Liposomes: A Nonviral Gene Delivery System for Cancer Therapy - Luiz, Marcela Tavares; Dutra, Jessyca Aparecida Paes [UNESP]; Tofani, Larissa Bueno [UNESP]; de Araújo, Jennifer Thayanne Cavalcante [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Marchetti, Juliana Maldonado; Chorilli, Marlus [UNESP] (MDPI, 2022)
Cancer is the second most frequent cause of death worldwide, with 28.4 million new cases expected for 2040. Despite de advances in the treatment, it remains a challenge because of the tumor heterogenicity and the increase in multidrug resistance mechanisms. Thus, gene therapy has been a potential therapeutic approach owing to its ability to introduce, silence, or change the content of the human genetic code for inhibiting tumor progression, angiogenesis, and metastasis. For the proper delivery of genes to tumor cells, it requires the use of gene vectors for protecting the therapeutic gene and transporting it into cells. Among these vectors, liposomes have been the nonviral vector most used because of their low immunogenicity and low toxicity. Furthermore, this nanosystem can have its surface modified with ligands (e.g., antibodies, peptides, aptamers, folic acid, carbohy-drates, and others) that can be recognized with high specificity and affinity by receptor overex-pressed in tumor cells, increasing the selective delivery of genes to tumors. In this context, the present review address and discuss the main targeting ligands used to functionalize liposomes for im-proving gene delivery with potential application in cancer treatment.
Keywords: active targeting; DNA; lipoplex; nonviral vector; nucleic acid; RNA